2019
DOI: 10.21608/svu.2019.23168
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multi-Drug Resistant Food-borne Bacteria in Ready-to-Eat Meat Products in Luxor City, Egypt

Abstract: A total of five Escherichia coli and eight Salmonella isolates were recovered from ready-to-eat meat samples obtained from different street vendors in Luxor city, Egypt. Bacterial isolates were assayed for antimicrobial susceptibility, its virulence and antimicrobial resistance genes. The total number recovered positive Salmonella spp and E. coli were 8 (6.66%) and 5 (4.16%) respectively. All E. coli isolates were exhibited resistance against streptomycin and cephalothin. While all Salmonella isolates were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In the present study, the prevalence of Salmonella in grilled chicken meat samples was 16/225 (7.1%, CI; 4.12% - 11.29%) (Table 1). These results are consistent with an Egyptian study in Luxor city which found that the isolation rate of Salmonella in ready-to-eat meat (RTE) samples was 6.67% (Younis et al ., 2019). However, a slightly lower rates were reported in Bangladesh (5%) and in Egypt (4.4%) where Salmonella prevalence in street food was 5 % (Abd- El–Malek, 2017; Khalif et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the prevalence of Salmonella in grilled chicken meat samples was 16/225 (7.1%, CI; 4.12% - 11.29%) (Table 1). These results are consistent with an Egyptian study in Luxor city which found that the isolation rate of Salmonella in ready-to-eat meat (RTE) samples was 6.67% (Younis et al ., 2019). However, a slightly lower rates were reported in Bangladesh (5%) and in Egypt (4.4%) where Salmonella prevalence in street food was 5 % (Abd- El–Malek, 2017; Khalif et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a Korean study found S. Enteritidis to be the dominant serovar (57%). Furthermore, a recent Egyptian study found S. Typhimurium and S. Enteritidis serovars to constitute 62.5% of detected salmonellae in ready-to-eat meat samples (Younis et al ., 2019). It is wellknown that ecological distribution of Salmonella serovars are subjected to various environmental factors (Chousalkar & Gole, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The lower ndings were done in India with the contamination rates of AMR E. coli (42%), Salmonella (9%), and Shigella (3%) and Egypt with the contamination rate of AMR Salmonella spp and E. coli were 8 (6.66%) and 5 (4.16%), respectively (17). The difference might be due to the study area, personal hygiene of the food handlers, food safety awareness of the food handlers, and sanitation condition of the food serving area.…”
Section: Discussionmentioning
confidence: 96%
“…Street foods are infected with bacteria and other microorganisms, making them dangerous for consumers' health (19). Street sold meals show an important part in meeting the food supplies of numerous individuals in under developed countries, and cherished by customers for their diversity, affordability and availability.…”
Section: Food Safetymentioning
confidence: 99%